Performance of the OraQuick Rapid Antibody Test for Diagnosis of Human Immunodeficiency Virus Type 1 Infection in Patients with Various Levels of Exposure to Highly Active Antiretroviral Therapy - O'Connell, Robert J.; Merritt, Teresa M.; Malia, Jennifer A.; VanCott, Thomas C.; Dolan, Matthew J.; Zahwa, Hassan; Bradley, William P.; Branson, Bernard M.; Michael, Nelson L.; De Witt, Caroline C. (Journal of Clinical Microbiology, 2003)
Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM